2000
DOI: 10.1111/j.1600-0781.2000.160301.x
|View full text |Cite
|
Sign up to set email alerts
|

UV‐induced immune suppression and sunscreen

Abstract: Sun protection factor (SPF) that measures sunscreen protection against erythema and edema may not be enough to measure a sunscreen's activity against many other biologic reactions induced by ultraviolet radiation (UV). It may be better to evaluate sunscreen efficacy using various tools including immune protection factor (IPF), mutation protection factor (MPF) and protection against photocarcinogenesis. In terms of immune protection, sunscreens protected against UV-induced immune suppression significantly. But … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…A variety of approaches have confirmed that UCA isomerization can be considered as an initiator of the complex pathway leading to immune suppression (1–3). Isomers of UCA in the skin have been determined by high‐performance liquid chromatography (HPLC) using the suction blister fluid (17), epidermal alkaline extract (18–22), or SC collected from adhesive tape (5, 20, 23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of approaches have confirmed that UCA isomerization can be considered as an initiator of the complex pathway leading to immune suppression (1–3). Isomers of UCA in the skin have been determined by high‐performance liquid chromatography (HPLC) using the suction blister fluid (17), epidermal alkaline extract (18–22), or SC collected from adhesive tape (5, 20, 23).…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent photoproducts are cycrobutane pyrimidine dimers and photoproducts. These DNA damages may induce cytokine dysregulation and immune suppression through the release of immune suppressive cytokines (1)(2)(3). UCA is another chromophore in the stratum corneum (SC).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…UVR‐induced skin effects include acute responses such as sunburn, pigmentation, hyperplasia, immunosuppression and vitamin D synthesis, and chronic effects, primarily photocarcinogenesis and photoaging (3–6). UVA wavelengths penetrate more deeply into the skin and are, therefore, more responsible than UVB for photoaging, wrinkling of the skin, and the formation of skin cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[1] The high-energy UV radiation that reaches us can ultimately cause visible sunburn of Nanotechnology the skin, erythema, photoaging, immunosupression, and photocarcinogenesis, among other adverse effects. [2] To prevent these adverse effects, sunscreens contain light-absorbing organic filters as well as lightreflecting and light-scattering inorganic nanoparticle filters. A combination of these two types of UV filters is necessary for broad-spectrum protection over the UVB and UVA ranges.…”
mentioning
confidence: 99%